Functioning of complex sentences in Vasyl Symonenko’s poetic language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The formal-grammatical structure and functional-stylistic potential of compound and complex sentences used in Vasyl Symonenko`s poetic works are analyzed. In particular, the peculiarities of the author's use of compound sentences, complex sentences, compound-complex sentences are described. It is proved that compound and complex sentences are an actively used component of Vasyl Symonenko's poetic syntax; they provide a connection between different structural elements of the poetic text, promoting its cohesion, and they also enhance the imagery and expressiveness of poetic language, help the author to represent the rich inner world of the character, convey the main idea of the poem to the readers. Compound and complex sentences in Vasyl Symonenko`s poems perform not only the functions of creating imagery but text production function. They provide semantic and structural connection between different elements of the text and contribute to the implementation of such important features as coherence, consistency and cohesion of the text. All of the described types of sentences enrich the imagery of poetic language, emphasize the depth of thoughts, help to convey the essence of poetic texts.
Keywords: compound sentence; complex sentence; clause; imagery; expressiveness